LEVERAGING FIRM PERFORMANCE THROUGH INFORMATION TECHNOLOGY STRATEGIC ALIGNMENT AND KNOWLEDGE MANAGEMENT STRATEGY: AN EMPIRICAL STUDY OF IT-BUSINESS VALUE - Yoshikuni, Adilson Carlos; Albertin, Alberto Luiz (International Journal of Research -GRANTHAALAYAH, 2020)
A central question for researchers and practitioners is whether and how knowledge management strategy (KMS) and information technology (IT) strategy alignment can help attain a competitive advantage. To address this question, this study draws on information strategic alignment (ITSA), and empirically examines the relationship between a firm’s KMS and IT on competitive performance. The survey examined empirical data from 225 Brazilian companies using the partial least squares path modeling to test the hypotheses proposed herein. The findings demonstrated that KMS exert significant, positive effects on ITSA, benefits of IT use (BUTI), business process performance (BPP), and firm performance (FP). The results suggest that researchers and practitioners should look beyond the direct effects on FP, and identify how KMS and ITSA can be leveraged to enable and support BPP, and thereby contributed to knowledge management strategy and IT business value literature.